On the Intrinsic Correlation Between Public Legitimation of Democratic Law and Discursive Competencies of Citizens - Cern, Karolina M. (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
The article discusses inter-correlations between conditions of democratic legitimation of modern law and discursive competencies of citizens as also individuals. The basic premises, on which the claim to the democratic legitimation of modern law is erected, are synthetically elaborated. On this basis discursive competencies are listed in short and their significance articulated with regard to so called weak – and strong public spheres. Crucially, the most fundamental change of basic premises on which democratic legitimation of modern law is contemporary thought of is clearly indicated.
Keywords: democratic legitimation of modern law; discursive competencies